Implikasi Novel Bumi Bidadari Karya Taufiqurrahman Al-Azizy Terhadap Pembelajaran Agama - Destiani Rahmawati (Jurnal Asy-Syukriyyah, 2018)
The researcher realizes that the story of Bumi Bidadari by Al-Azizy has moral value in that novel. The story told about Fatimah Az-Zahra has unique character. She is introvert woman. She is the main character. This research has religious elements to investigate and description of data in Bumi Bidadari novel. The instrument of collecting data was descriptive method with structural and objectivity of the story. The result has domination with religious element including sharia dimension is 42,5 %, character dimension is 35,0% dimension of faith is 22,5 %. It can be seen the topic of the story has moral value which describe religious value of each person’s likes; Labib as religion teacher, Pras, Hasyim. The story told about sharia, character, faith dimension.